Laccases repertoire of a subterranean termite coptotermes curvignathus holmgren (blattodea: rhinotermitidae) - Hoe, Pik Kheng; King, Jie Hung; Ong, Kian Huat; Bong, Joseph Choon Fah; Mahadi, Nor Muhammad (Universiti Kebangsaan Malaysia, 2019)
Coptotermes curvignathus is a subterranean termite species that vigorously feed on living-tree. The cellulose, hemicelluloses, lignin components in the wood are too robust for many organisms to break down and extract energy from but they serve as main carbon and energy sources for C. curvignathus. The ability of this subterranean termite thrive on wood diet may attribute by its array of laccase repertoire. Laccases are known for many functions including detoxification of plant tissues via xenobiotic pathway, and most importantly for termite is lignin modification. This paper highlighted the type of laccases produced by C. curvignathus based on transcriptomic data that were generated from 500 termites’ digestive system using Illumina HiSeq 2000. Raw data was trimmed and assembled by SOLEXAQA and Bowtie before loaded into Gene Ontology based data mining software, Blast2GO (B2G). The result showed that, C. curvignathus expressed diverse laccase genes that were phylogenetically similar to other termites’ laccases and distinctly related to fungal or bacterial laccases. Other than providing laccase genes sequences for further gene and enzyme characterization, the result of this study is the first insight into C. curvignathus laccase repertoire that is important to elucidate how C. curvignathus could digest wood efficiently from either intact or partially hydrolyzed wood.